The effect of spiritual well-being scale level on general comfort in patients with two different chronic diseases (HF, COPD) - Ummuhan Akturk; Behice Erci (Acta Scientiarum. Health Sciences)
This research was conducted to compare the spiritual beliefs and comfort levels of patients with heart failure (HF) and chronic obstructive pulmonary disease (COPD). This research was conducted between January- November 2021 a Hospital in City Center. The research population comprises (HF), (COPD) patients hospitalized a Hospital in the City. In the study, 232 patients were reached. In the study, data were collected from the patients with the survey, Spiritual Well- being Scale and General Comfort Scale, during weekdays, using face-to-face interview technique with patients in their rooms. When we look at the effect of Spiritual Beliefs on General Comfort level in 2 chronic disease groups in the study, it is seen that Heart Failure patients with 13.7% and Chronic Obstructive Pulmonary patients 0.19%. In the study, the effects of psychological beliefs and socio-demographic characteristics on the comfort level of patients with heart failure and those with chronic obstructive pulmonary disease are higher.